Antarctica the last continent - Tobias, Michael; Film for the Humanities and Sciences (Princeton, NJ : Films for the Humanities & Science, 1987)
This program introduces the geography of this continent and contrasts the beauty of the icescape with the discovery made here of the potentially lethal hole in the atmosphere that exposes us to carcinogenic levels of ozone
Title from title screen
Executive producer, Ken Ellis ; camera, Stuart Keene
Narrator: Bob Jimenez
Keywords: Antarctica; Antarctica -- Discovery and exploration; Antarctica -- History